Gaya Ilustrasi Damar Kurung Pada Konsep Desain Brand Identity Sebagai Daya Tarik Visual Kemasan Sapit Bandeng Bu Amiroh Gresik dan Strategi Promosi - Silvi Firma Silvi Alif; Taufik Murtono Murtono (CITRAWIRA : Journal of Advertising and Visual Communication, 2021)
Sapit Bandeng is a typical food from the Gresik region, one of the producers is Mrs. Amiroh. This study aims to design a brand identity and promotion of milkfish sapit Mbok Amiroh-Gresik. The creation process carried out at the stage of making this work uses field research methods, namely direct observation, making alternative designs, selecting designs, applying designs, and final art work. The design is adapted from the illustration of Damar Kurung which is the mascot of Gresik City. This design resulted in the main logo and packaging designs as well as stationaries, merchandise, advertisements in the Jawa Pos newspaper, and mural advertisements on the walls as part of the promotional strategy.